Innovative Approach: Exploring the Efficacy of Red Ginger Infusion Therapy in Hypertension Management - Sridani, Ni Wayan; Muh Sabir; Fauzan; Ratna Devi; Arifuddin, Adhar; Rahman, Abd; Nur, A Fahira (YCAB Publisher, 2025)
Background:Hypertension is a serious global health issue due to its rising prevalence and its link to severe cardiovascular diseases. Red ginger (Zingiber officinale var. rubrum)infusion therapy has gained attention as a potential natural treatment for high blood pressure because of its active compounds, such as gingerols and shogaols, which have anti-inflammatory and vasodilatory effects. Objectives:This study investigates the effectiveness of red ginger infusion therapy in reducing hypertension among residents of Kawatuna Village, where hypertension rates reached 12.2% in 2022. Given the community’s dietary habits and limited healthcare access, alternative treatments like this are important for managing blood pressure. Methods:The study used a Quasi-Experimental design with a Pretest-Posttest Control Group approach. A total of 66 participants were divided into an experimental group and a control group. The experimental group consumed red ginger infusion daily for seven days, while the control group received no intervention. Blood pressure was measured before and after the intervention. Results:The results showed a significant decrease in blood pressure in the experimental group. Systolic pressure dropped by an average of 24 mmHg and diastolic pressure by 11 mmHg (both p<0.001). In contrast, the control group had only slight changes, with a decrease of 0.17 mmHg in systolic pressure and 1.1 mmHg in diastolic pressure. These findings suggest that red ginger infusion therapy can effectively lower blood pressure in the short term. However, the small sample size and short duration of the study highlight the need for further research. Future studies should explore the specific mechanisms behind red ginger’s effects and assess its long-term safety and efficacy. Addressing lifestyle factors, like the high consumption of coconut milk in Kawatuna, through health education programs could also improve hypertension management. Conclusion:Red ginger infusion therapy shows promise as a complementary treatment for hypertension, but more comprehensive studies are needed to confirm its long-term benefits. Keywords: red ginger; hypertension; infusion therapy, blood